Vitamin D: An overview - Clifopoulos, Chris (Mediterr J Rheumatol, 2017)
The role of Vitamin D is examined in skin with regards to synthesis and neoplasia. Despite its evolving role in bone health undefined benefits with regards to other disease such as neoplasia and skin cancer are under scrutiny. A brief overview is presented with formalised advice to patients regarding skin cancer, and Vitamin D requirements in the clinical setting. Given that weather conditions in Australia and the Mediterranean climates share similarities, some parallels can be drawn from the Australian experience for Europe.